Beyond the Principle of Proportionality: Controlling the Restriction of Rights under Factual Uncertainty - Borja Sánchez Barroso (Oslo Law Review)
The principle of proportionality is considered the main legal tool to control restrictive measures of rights, both in ordinary courts and at a constitutional level. In addition to its general limitations, new shortcomings of the principle have played a central role during the pandemic, questioning the principleʼs efficacy in situations of factual uncertainty, especially in technically or scientifically complex contexts. This article analyses this efficacy problem and exemplifies it with specific measures adopted to prevent COVID-19. It also analyses potential ways to counter those shortcomings, such as refining the principle itself, emphasising judicial deference to legislative and executive powers, or adopting prior decisions as to the information that must be taken into account in case of uncertainty. Finally, the article proposes some additional checks that could complement the culture of justification promoted by the principle and strengthen the control of public powers when restricting rights under conditions of uncertainty.